Analisis Lean Manufacturing Produksi Saus Gulai dengan Metode Value Stream Mapping - Rifky Khoeruddin; Dias Indrasti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
Work productivity can be improved by minimizing waste on the production line. This study aimed to identify the flow process, evaluate constraints and waste, and design improvements in curry sauce production. Using Value Stream Mapping based on Lean Manufacturing principles, the study analyzed the production process through three stages: (1) current state mapping; (2) identification of constraints and waste; and (3) development of a future state map. The waste identified on the production line included worker/product movement, waiting time, and overproduction, resulting in a total lead time of 25621.4 seconds. Future state improvements, such as the implementation of Standard Operational Procedures (SOP), optimization of worker numbers, maintenance of equipment, and use of efficient machines, reduced the lead time to 25018.2 seconds. The study demonstrates the potential for increased productivity and resource/energy utilization through production line improvements.